Particles Interactions in Composites Reinforced by Fibre and Spherical Inclusions - Milan Zmindak; Pavol Novak (Communications - Scientific letters of the University of Zilina, 2009)
In our contribution we will show a new Method of Continuous Source Functions (MCSF) to modelling of such problems like composites reinforced by ﬁnite length ﬁbres with a large aspect ratio and composites reinforced by spherical inclusions. The source functions (forces and dipoles) are continuously distributed along the ﬁbre axis (i. e. outside of the domain, which is the domain of the matrix) and their intensities are modelled by 1D quadratic elements along the axis in order to satisfy continuity conditions between the matrix and ﬁbre. The spherical inclusions are modelled by a triple dipole located in the centre of the particle and the intensities of the dipole can be computed using a small number of collocation points on the particle boundary.